STRATEGI PENGEMBANGAN SDM DALAM PENDIDIKAN ISLAM: TINJAUAN LITERATUR - Yusra, Helsa; Astuti Darmiyanti; Saprialman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze human resource development (HRD) strategies in Islamic education through a literature review approach. This research uses a qualitative method with a literature study, where data are collected from various relevant academic sources such as journals and books, and then analyzed descriptively. The results show that human resource development in Islamic education is not only focused on improving professional competencies but also on strengthening character and spiritual values. HRD strategies are implemented through training and development, career development, performance evaluation, as well as modern approaches such as talent management and sustainable human resource practices. In addition, the quality of human resources is influenced by internal, external, and organizational factors. The impact of HR development can be seen in improving individual performance, institutional quality, and organizational competitiveness in a sustainable manner.